Muzakki's Trust in Paying Zakat through BAZNAS South Solok Regency is Influenced by Principles of Good Corporate Governance - Fransiska, Arina; Basra, Sri Meiweni; Azizah, Rahmi Nur (UPI YPTK Journal of Business and Economics, 2024)
This research is based on the low interest of muzakki in the South Solok area to pay zakat through zakat institutions, namely Baznas, and the important role of the principles of good corporate governance, such as transparency and accountability of zakat institutions in influencing the trust of muzakki to pay zakat through Baznas. This research aims to prove the influence of transparency and accountability of zakat institutions on muzakki's trust in paying zakat through Baznas, South Solok Regency, partially and simultaneously. The research population came from muzakki registered with Baznas, South Solok Regency. Sampling was carried out randomly and specific criteria for muzakki were not determined. The number of samples processed in this study was 98 people. Data analysis used the t-test and F-test with the help of the SPSS program. This research proves that institutional transparency and accountability significantly influence muzakki's trust in paying zakat through Baznas South Solok Regency, and the influence obtained is partial and simultaneous.